2022
DOI: 10.21834/ebpj.v7isi9.4304
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Artificial Intelligence using Automated Writing Evaluation for Writing Skills

Abstract: This study aims to investigate the effectiveness of AI software which is Automated Writing Evaluation (AWE) in detecting grammatical errors in improving writing skills among Malaysian public university students and examine their perceptions of AI software in improving writing skills. The findings of this study show the positive perceptions of students towards the implementation of AWE. The study provided implications for the effective use of AI software (AWE) in ESL writing classrooms. Finally, future research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…AI's integration in oral practice and writing exercises brings to the light its potential to elevate language learning experiences. Rahman's recent study [23] reinforced the effectiveness of AWE in pinpointing grammatical errors and improving writing proficiency among Malaysian university students. Collectively, these research findings strongly advocate for integrating AI, particularly AWE, as a valuable tool for enhancing writing skills.…”
Section: Fig 1: Literature Review From Elicit Aimentioning
confidence: 90%
“…AI's integration in oral practice and writing exercises brings to the light its potential to elevate language learning experiences. Rahman's recent study [23] reinforced the effectiveness of AWE in pinpointing grammatical errors and improving writing proficiency among Malaysian university students. Collectively, these research findings strongly advocate for integrating AI, particularly AWE, as a valuable tool for enhancing writing skills.…”
Section: Fig 1: Literature Review From Elicit Aimentioning
confidence: 90%
“…In addition, the utilization of AI in language instruction, exemplified by ChatGPT and other AI models, has clearly demonstrated its effectiveness in enhancing English writing proficiency. Recent research has shown the value of AI-driven systems in enhancing the grammar, syntax, vocabulary use, and coherence of writing (Rahman et al, 2022). As a cutting-edge language model, ChatGPT can offer learners detailed insights into their writing abilities and places for progress through real-time feedback on written compositions (Bishop, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The participant agrees with ChatGPT's consistent overall assessment based on different writing criteria set by the lecturer. Within a click, it gives a full and detailed description of students' errors, especially in lexical use, structures, and syntax (Rahman et al, 2022), which helps save a great deal of time and effort in detecting errors and giving feedback to the students. Within 1 minute for an essay's grading and comment, it costs just one hour and 40 minutes for 100 essays in comparison with 45 minutes spent by the lecturer for one essay.…”
Section: Lecturer's Perspectives Towards the Use Of Ai Tool (Chatgpt)...mentioning
confidence: 99%